Review of Shakespeare in the Worlds of Communism and Socialism, edited by Irena R. Makaryk and Joseph G. Price (Toronto: University of Toronto Press, 2006) - Lupić, Ivan (Array, 2008)
Review of a collection of essays devoted to the problems of Shakespeare reception in the worlds of Communism and Socialism.